Analysis of SOLO taxonomy-based test instruments in approaching the Merdeka curriculum - Yuanita, Putri; Maimunah, Maimunah; Kartini, Kartini; Arif, Nur (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2023)
Students' ability in Indonesia has decreased due to the COVID-19 pandemic, so the Government provides solutions to restore learning in Indonesia through a Merdeka curriculum. The impact on schools, especially mathematics subjects, decreased mathematical problem-solving abilities. The decreasing ability of students to solve problems requires a test instrument based on the SOLO taxonomy. The formative research model is the type of this research. The stages in the model are preliminary and formative evaluation. Stages such as self-evaluation, expert review, one-to-one, small group, and field tests are the stages in formative evaluation. Based on the validation results of the four validators, the average score of the material aspect validation results is 94% with a very valid category, the average score for the constructed aspect is 87% with a very valid category, the average score for the language aspect is 92% with a very valid category, and the average score of all aspects is 91% with a very valid category so that the test instrument developed is categorized as very valid. The trial subjects in this study were conducted at SMAN 15 Pekanbaru, SMAN 12 Pekanbaru, MAN 3 Pekanbaru and SMA Plus Pekanbaru. Quantitative data is used as data analysis in this study. The research results that have been carried out from 20 questions, obtained from as many as 18 questions based on the SOLO taxonomy, have been tested and declared valid and reliable with a Cronbach's Alpha value of 0.871.